151 quick ideas for delegating and decision making - Dittmer, Robert E., 1950-; McFarland, Stephanie, 1968- (151 quick ideas., 2018)
151 Quick Ideas for Delegating and Decision Making combines 50 years' experience of two managers, and the experiences of other managers who have been interviewed and observed.